Analysis of Competence and Independence of Internal Auditor on Internal Audit Quality - Anggraini, Leriza Desitama (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2020)
Research is conducted with the aim of analyzing competencies and independence affecting the quality of audits in the company. The company's extensive scope restricts management and the board of directors from conducting direct oversight of internal and external activities in each of the company's operational activities. Therefore, management and the board of directors need a task force tasked with overseeing and examining the company's operational activities in order to improve internal control effectively and efficiently. There are still many problems of independence among internal auditors to date due to the position of internal Auditor working for management or working for the company. Research is carried out with a quantitative approach and with descriptive methods. The design of the research is a case study. Data collection techniques are carried out by questionnaire method and document inspection. Based on the results of the study concluded there is an influence of competence and independence on the quality of internal audits.